Comparative Analysis of Graphene and Conventional Coatings for Enhancing Aluminum Busbars’ Electrical Conductivity and Corrosion Resistance - Çevik, Mehmet; Elvan, Onur (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
This study explores the use of graphene coatings to enhance the electrical conductivity and corrosion resistance of aluminum busbars. Graphene was synthesized via Chemical Vapor Deposition and transferred onto aluminum, with comparisons made against bare and tin-coated samples. A single graphene layer significantly increased surface conductivity, achieving 11 times better performance than tin-coated and 33 times better than uncoated aluminum before corrosion. Characterization using Raman spectroscopy, resistivity measurements, and wettability tests confirmed successful graphene synthesis and transfer. Long-term performance was tested in NaCl solution, where graphene-coated samples exhibited only a 10.71% resistance increase, compared to 21.80% for tin-coated and 197.90% for uncoated aluminum. Initially, graphene improved water repellency, but after corrosion, the samples became hydrophilic. Despite its limitations in maintaining durability under harsh conditions, graphene proves highly effective in improving aluminum’s electrical and anti-corrosive properties, with potential for further optimization.